2021
DOI: 10.1088/1755-1315/714/2/022058
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Information Disclosure in The Network Environment

Abstract: Facing global warming and environmental problems, enterprises should fulfill their environmental responsibilities in protecting the environment, reducing carbon emissions and improving environmental quality. With the development of computer network technology and the promotion of 5G technology, carbon information disclosure has become intuitive and individualized, which will, to a great extent, help enterprises disclose carbon information in a timelier manner. Based on the current situation of carbon informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Foreign scholars have conducted studies on how enterprises should carry out CAID and what the specific scope involves. In their study, Wu, D. [8] suggested that carbon accounting information is not the same as carbon accounting, but the former has a broader scope and includes information on climate change. Wang, Y.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign scholars have conducted studies on how enterprises should carry out CAID and what the specific scope involves. In their study, Wu, D. [8] suggested that carbon accounting information is not the same as carbon accounting, but the former has a broader scope and includes information on climate change. Wang, Y.…”
Section: Introductionmentioning
confidence: 99%